RESPON DUA VARIETAS KUBIS BUNGA TERHADAP KOMBINASI PEMBERIAN PUPUK KANDANG DAN PUPUK HAYATI PADA TANAH ALUVIAL DENGAN SISTEM BUDIDAYA JENUH AIR - Fitriani, Suweni; Basuni, Basuni; Nurjani, Nurjani (Fakultas Pertanian, Universitas Janabadra, 2024)
Cultivation of cauliflower in West Kalimantan has high prospects for cultivation, especially on alluvial soil. However, cultivation of cauliflower on alluvial soil is faced with the constraint of soil pH which causes land productivity to decrease. Proper cultivation techniques and soil conditioners are needed to increase soil fertility so that land productivity increases. This study aims to obtain the best combination of manure and biological fertilizer doses that affect the growth and yield of cauliflower cultivation of Snow White and Larissa varieties and to determine which cauliflower varieties respond better after being treated. The study was conducted at the Golden River Camp land, Jalan Kalimas Tengah, Dusun Mawar, Kalimas Village, Sungai Kakap District, Kuburaya Regency, West Kalimantan Province. The study was conducted from July to November 2023. This study used a Split Block design. The main plot is the cauliflower variety (V) consisting of v1 = Larissa, v2 = Snow White and the subplot is a combination of manure and biological fertilizer (S) consisting of s1 = chicken manure, s2 = goat manure, s3 = chicken manure + biological fertilizer, and s4 = goat manure + biological fertilizer. There are 2 factors with 4 treatments. Each treatment consists of 3 replications so that there are 24 treatment units with each treatment unit determined by 4 plant samples and among the 4 plant samples determined by 1 destructive plant. The variables observed in this study include the number of leaves, leaf area, fresh plant weight, dry plant weight, flower emergence, crop diameter, and crop weight. The results showed that the interaction between the combination of manure and biological fertilizer on cauliflower varieties had a significant effect on crop diameter. The combination of ameliorants on the Larissa variety did not provide any difference in the growth and yield of cauliflower, while on the Snow White variety, the combination of ameliorants provided a difference in the yield of cauliflower plants. The combination of chicken manure + biological fertilizer and goat manure + biological fertilizer treatments on the Snow White variety gave better results than the treatment of chicken manure and goat manure on the growth and yield of cauliflower.